Evaluation of YouTube Videos on HIV/AIDS: A Critical Analysis of Content Quality and Reliability - Semet, Cihan (Brazilian Journal of Sexually Transmitted Diseases, 2023)
HIV and AIDS remain as significant global health issues, with misinformation and stigma surrounding the diseases still being prevalent. Accurate and reliable information is crucial for promoting prevention, early detection, and effective management of the disease. YouTube has emerged as a popular platform for sharing and consuming health-related content, but the quality and reliability of its videos on various health topics have been questioned. Objective: This study aims to systematically review and evaluate the quality and reliability of YouTube videos on HIV/AIDS. Methods: We searched for videos on YouTube using two search terms, "HIV" and "AIDS," and evaluated the top 100 videos for each search term. We recorded video features such as length, likes, comments, views, and upload date. Two independent evaluators assessed the videos’ quality and reliability using the Global Quality Scale and the modified DISCERN tool. We classified the videos into two groups based on the source that uploaded the video, professional and non-professional, and analyzed the data using statistical methods. Results: Of the 159 videos evaluated, the most common content categories were HIV transmission routes, basic information and definition of HIV, and HIV/AIDS activism and awareness. Non-professional videos tended to be shorter, but there were no significant differences in views, likes, and likes per day counts. Comments were significantly higher in non-professional videos. Professional videos had higher quality and reliability scores than non-professional videos. Conclusion: Accurate and reliable information on HIV/AIDS is critical for promoting prevention, early detection, and effective management of the disease. YouTube has the potential to disseminate this information, but the quality and reliability of its videos must be improved. Our study highlights the need to prioritize professional, high-quality, and reliable video content on HIV/AIDS on YouTube to improve the public health outcome.